Field evidence for transfer of plastic debris along a terrestrial food chain. Issue 1 (December 2017) - Huerta Lwanga, Esperanza; Mendoza Vega, Jorge; Ku Quej, Victor; Chi, Jesus; Sanchez del Cid, Lucero; Chi, Cesar; Escalona Segura, Griselda; Gertsen, Henny; Salánki, Tamás; van der Ploeg, Martine; Koelmans, Albert; Geissen, Violette
Abstract Although plastic pollution happens globally, the micro- (<5 mm) and macroplastic (5–150 mm) transfer of plastic to terrestrial species relevant to human consumption has not been examined. We provide first-time evidence for micro- and macroplastic transfer from soil to chickens in traditional Mayan home gardens in Southeast Mexico where waste mismanagement is common. We assessed micro- and macroplastic in soil, earthworm casts, chicken feces, crops and gizzards (used for human consumption). Microplastic concentrations increased from soil (0.87 ± 1.9 particles g−1 ), to earthworm casts (14.8 ± 28.8 particles g−1 ), to chicken feces (129.8 ± 82.3 particles g−1 ). Chicken gizzards contained 10.2 ± 13.8 microplastic particles, while no microplastic was found in crops. An average of 45.82 ± 42.6 macroplastic particles were found per gizzard and 11 ± 15.3 macroplastic particles per crop, with 1–10 mm particles being significantly more abundant per gizzard (31.8 ± 27.27 particles) compared to the crop (1 ± 2.2 particles). The data show that micro- and macroplastic are capable of entering terrestrial food webs.